The quality and effectiveness of interventions that target multiple risk factors among young people: a systematic review. (13th September 2016) - Knight, Alice; Shakeshaft, Anthony; Havard, Alys; Maple, Myfanwy; Foley, Catherine; Shakeshaft, Bernie
Abstract: Objective: To identify evaluations of interventions that target multiple risk factors in high‐risk young people, describe their characteristics, critique their methodological quality and summarise their effectiveness. Methods: A search of the literature published between 2009 and 2014 identified 13 evaluations of interventions that targeted multiple risk factors, compared to 95 evaluations that targeted single risk factors. The methodological adequacy of the 13 evaluation studies was analysed using the Quality Assessment Tool for Quantitative Studies and information regarding characteristics and intervention effectiveness was extracted and summarised. Results: There were very few outcome evaluation studies of interventions that targeted multiple risk factors, relative to single risk factors, among high‐risk young people. Of the identified studies, half were methodologically weak. Interventions delivered in community settings targeted a greater number of risk factors, while those delivered in a school or health setting reported a higher proportion of statistically significant outcomes. No economic analyses were conducted. Conclusions and Implications for Public Health: More methodologically rigorous evaluations of interventions targeting multiple risk factors among high‐risk young people are required, especially for those delivered in community settings. Four key areas for improvement are: i) more precisely defining the risk factors experienced by high‐risk young people; ii) achieving greater consistency across interventions; iii) standardising outcome measures; and iv) conducting economic analyses.